Haemodynamic effects of percutaneous mitral valve edge-to-edge repair in patients with end-stage heart failure awaiting heart transplantation - Geis, Nicolas; Pleger, Sven Torsten; Bekeredjian, Raffi; Chorianopoulos, Emmanuel; Kreußer, Michael; Frankenstein, Lutz; Ruhparwar, Arjang; Katus, Hugo; Raake, Philip (ESC heart failure, 2018)
Aims Functional mitral regurgitation is complicating end-stage heart failure and potential heart transplantation by increasing pulmonary artery pressures. The aim of the present study was to investigate feasibility and haemodynamic effects of percutaneous mitral valve edge-to-edge repair using the MitraClip™ device in patients with end-stage heart failure awaiting heart transplantation. Methods and results In this retrospective study, we identified nine patients suffering from end-stage heart failure listed for heart transplantation in whom moderate-severe or severe functional mitral regurgitation was recognized and treated with percutaneous mitral valve edge-to-edge repair. Twenty-two patients listed for heart transplantation and presenting with moderate-severe or severe functional mitral regurgitation treated in the pre-MitraClip™ era served as controls. Patients were analysed at two separate time points: MitraClip™ group: pre-procedure and post-procedure (follow-up: 215 ± 53 days) and control group: study entry with recognition of moderate-severe or severe functional mitral regurgitation (follow-up: 197 ± 47 days). Percutaneous mitral valve edge-to-edge repair with the MitraClip™ was feasible and safe in our high-risk end-stage heart failure population. The intervention resulted in significant reduction of mitral regurgitation (grade 3.0 [0.5] to 1.5 [0.5]; P = 0.009), left atrial diameter (51 mm [16] to 49 mm [4]; follow-up MitraClip™ vs. control group P = 0.0497), pulmonary artery pressures (sPA 50 mmHg [15] to 45 mmHg [10]; P = 0.02; mPA 34 mmHg [8] to 30 mmHg [10]; P = 0.02), and New York Heart Association class (3.5 [1.0] to 3.0 [0.5]; P = 0.01) and improved mixed-venous oxygen saturation (57% [11] to 55% [7]; follow-up MitraClip™ vs. control group P = 0.02). No changes in the control group were observed. Conclusions MitraClip™ implantation as ‘bridge-to-transplant’ strategy in patients with end-stage heart failure and severe functional mitral regurgitation awaiting heart transplantation is feasible and appears to result in favourable haemodynamic effects.
Gesehen am 26.09.2019